(untitled) (KULT_online, 2021)
This study weaves together three movements of a Colombian feminist’s decolonial praxis. First, Rodríguez Castro engages with decolonial feminisms to dismantle colonial feminisms in Latin America. Second, the author reflects on the sentipensante commitment she uses to delve into rural places as a White-mestiza. Third, she forges dialogues with rural women and social leaders to intertwine politics of place with insurgencies spawned by rural women’s experiences and to advocate their participation in post-conflict negotiations embedded in persistent violence.